The neonatal mortality and hospitalization rate among high-risk neonates who underwent home care services - Reza Khadivi; Shadi Mirzaeian; Raheleh Toghyani (Wolters Kluwer Medknow Publications, 2022)
Background: Low birth weight neonates often require intensive care. However, in the absence of resources, Home Care (HC) could replace theoretically the essential health care. HC was presented for high-risk neonates who were born in 2016 in Isfahan city as a national pilot study. The aims of this study were to evaluate the Neonatal Mortality Rate (NMR) and hospitalization rates in the HRNs who received HC during the neonatal period. Materials and Methods: In a cohort study without a control group that was performed during 2016-2017, 130 HRNs who received HC in the neonatal period in Isfahan city were evaluated during 1 year. Data about the neonates' gender, age, birth weight, gestational age, congenital anomalies, cause of death (in terms of prematurity and related problems), and age at death were gathered and analyzed using the Chi-square test, independent t-test, Mann-Whitney U test, and multiple linear regression tests. Results: Out of the 129 HRNs who had received HC and completed a 1-year follow-up period, one neonatal death occurred due to multiple anomalies. In this way, the NMR was estimated as 7.75 per 1000 live neonates. In addition, 86 cases (66.66%) were hospitalized for one time in the neonatal period, 10 (6.14%) cases for the second time, and one HRN for the third time for 10 days. Conclusion: About one-third of the HRNs who had previously received HC in the neonatal period did not require inpatient care. In addition, the neonatal and infant mortality rates were low.